Managerial Competency of School Principles in Improving the Performance of Teachers and Educational Performances in School: School Principles in Improving The Performance - Agus, Sutarman; Sukanti, Lina; Rohaeni, Anie; Sulastri, Neneng (Future Science, 2022)
The purpose of this research is to know (a). Principal Managerial Competence (b). Knowing the Relationship between Principal Managerial Competencies in Improving Teacher Performance and Education Personnel (c). Knowing the Obstacles in Improving the Performance of Teachers and Education Personnel. This research method uses a qualitative approach, which describes the findings and phenomena that occur. Data collection techniques through (1). Interview (2). Surveys (3). Documentation studies are in the form of searching data in the form of archives, pictures, photos, meeting notes. Conclusion (1). The managerial competence applied by the principal is in accordance with the functions and managerial competencies of the principal adopted (2). The relationship between the principal's competence and teachers and education staff, as a managerial competence, the principal has a role in planning programs according to the needs of teachers and education personnel (3). The principal obstacle in improving the performance of teachers and education personnel is the family factor and the remote location of the training